Contemporary Issues in Women's Health. Issue 1 (17th November 2019) - Geary, Michael; Chibwesha, Carla; Stringer, Elizabeth
Abstract : Should ursodeoxycholic acid be used for management of Obstetric Cholestasis? The PITCHES trial Hypertension in pregnancy: reducing maternal morbidity and mortality Training the Next Generation of Women's Health Practitioners and Leaders in LMICs.